2008
DOI: 10.1007/s10643-008-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Image of the Singapore Child

Abstract: The purpose of this study was to analyse the contents of one of the leading newspapers of Singapore in an effort to identify the public image of the children of the nation. Newspaper clippings of news/articles, pictures/ photographs and advertisements featuring children below 15 years of age were collected over a one-week period and the content analysed in an attempt to find out the extent to which children in Singapore are visible and how they are portrayed in the media. While it is impossible to generalise t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In a study conducted by Ebbeck and Warrier (2008), to identify the image of the Singapore child by analysing the contents of one of the leading newspapers of the nation, it was found that children were predominantly portrayed as passive and vulnerable, needing adult attention. The visibility of children in the media was low compared with their total presence in the population.…”
Section: Who and What Of Children In Singapore?mentioning
confidence: 99%
“…In a study conducted by Ebbeck and Warrier (2008), to identify the image of the Singapore child by analysing the contents of one of the leading newspapers of the nation, it was found that children were predominantly portrayed as passive and vulnerable, needing adult attention. The visibility of children in the media was low compared with their total presence in the population.…”
Section: Who and What Of Children In Singapore?mentioning
confidence: 99%
“…In terms of reforming early childhood curriculum in the cultural context of Singapore, there is an urgent need to bring in the SEL component, which is valuable for preparing them to meet the challenges they will inevitably face in daily activities and lifelong pursuits. As the image of Singapore child is always characterised as being passive and incapable of expressing opinions on matters (Ebbeck and Warrier, 2008), more SEL opportunities will enable them to build relationships, practice social skills and become active and responsible citizens. Furthermore, the academic-focused culture has been evident in Singapore’s early childhood sector, with teachers and parents prioritising academic areas in young children’s learning (Bautista et al., 2016; Clarke and Sharpe, 2003).…”
Section: Conclusion Limitations and Implicationsmentioning
confidence: 99%
“…They also believe that some parents enrol their children in enrichment and tuition classes and hence, preschools are expected to raise the bar to keep up with the children's higher levels of academic skills (Yongbeon & Fung, 2021). This, in turn, has placed pressure on primary schools to raise the bar as well, resulting in spiralling levels of stress placed on the children, parents and teachers in both the preschools and primary schools (Bach & Christensen, 2017;Ebbeck & Chan, 2011;Ebbeck & Warrior, 2008;Lim-Ratnam, 2013). An over emphasis on school readiness skills and employing primary school teaching methods has also led to the 'schoolification' of some preschools in Singapore (Gunnersdottir, 2004, p.1).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ebbeck & Warrior (2008), this phenomenon could be attributed to Singapore being a "result-oriented, exam focused education system" (p. 248). Similarly, Lim-Ratnam (2013) also believes that the pressures of Singapore's high-stakes examination system in schools have contributed to a strong emphasis on academic skills in the preschools and schools.…”
Section: Introductionmentioning
confidence: 99%